Recrudescence of a high parasitaemia, severe Plasmodium falciparum malaria episode, treated by artesunate monotherapy. (April 2021) - Landre, Sophie; Bienvenu, Anne-Lise; Miailhes, Patrick; Abraham, Paul; Simon, Marie; Becker, Agathe; Conrad, Anne; Bonnot, Guillaume; Kouakou, Yobouet Ines; Chidiac, Christian; Leboucher, Gilles; Rimmelé, Thomas; et al.
Graphical abstract: Highlights: A patient with severe malaria suffered a severe recrudescent episode. Artesunate monotherapy is associated with a higher risk of recrudescence. Hyperparasitaemia is associated with a higher risk of recrudescence. Parasite clearance time is an indicator of recrudescence risk. Antimalarial stewardship programs are needed to promote good clinical practices. Abstract: A patient presenting with severe malaria, with hyperparasitaemia, received 7-day artesunate monotherapy. A severe recrudescence was detected and attributed to hyperparasitaemia, monotherapy and a polyclonal infection without Kelch 13 gene mutation. A second treatment with artesunate, then quinine, followed by artemether-lumefantrine, was successful.